HABITS OF TOOTH BRUSHING AND TOBACCO/ BETEL NUT USE AMONG PATIENTS ATTENDING DENTAL OUTPATIENT DEPARTMENT IN A TEACHING HOSPITAL - Shaikh, Muhammad Saad; Lone, Mohid Abrar; Khan, Muhammad Sibghatullah; Iqbal, Kefi; Siddiqui, Saad Uddin; Abrar, Syed Kashif; Allana, Raheel; Kumar, Love Kesh (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: To investigate the use of tobacco/betel nut and frequency of tooth brushing in males and females reporting to OPD. METHODOLOGY: A cross-sectional survey was carried out on 600 patients attending the Dental OPD of Sindh Institute of Oral Health Sciences (SIOHS) in Karachi from January to March 2019. After obtaining informed consent from all participating subjects, data regarding tobacco/betel nut use and frequency of tooth brushing were recorded by the investigator. Data analysis was done using SPSS version 20.0 (SPSS Inc., USA). RESULTS: Regarding use of tobacco, more females were using smokeless tobacco (40%), whereas more males smoked cigarettes (27%). In terms of tooth brushing, greater proportion of non-tobacco users (54.7%) had better brushing habits compared to smokeless tobacco and cigarette smokers (26.7% and 17.5 % respectively).Regarding frequency of tooth brushing, more non-tobacco users (53%) brush or miswak at least once a day compared to tobacco users. Additionally, there is a significant difference in frequency of brushing habit between males and females (22.1% and 43.2 % twice a day respectively) suggesting that females have better brushing habits. A statistically significant association was seen between tobacco users and brushing habit using Chi-Square test (p < .001). CONCLUSION: Patients using tobacco reported poor oral hygiene practices than non-users. Patients using tobacco (cigarette smokers and smokeless tobacco) should be identified separately and oral hygiene measures reinforced as part of routine dental practice. KEYWORDS: Tobacco, Tooth brushing, Oral hygiene, Smoking